The defense of Rejneesh’s idea of inconsistency in scholars : the rejection of rigidity in academia - Ntshangase, Mohammed Xolile (My University, 2023)
Although it is the nature of the world that things always change except the change itself, some scholars have become ideological in the strife for consistency. Some scholars take their ideas as sacred to the effect of sticking by them even when they are no longer sufficiently defensible. This fear of being inconsistent has crept even into the minds of scholars. Bagwan Rejneesh, an Indian philosopher who was always comfortable with changing and embracing change became vital as an advocate of thought development. This defense presents the necessity of being not resistant to change due to what one has held before. There has been a contradiction within the academic thoughts projected by some scholars. The center of the contradiction stems from scholars’ arguments for evolution and transformation while at the same time, they worry about being always consistent. Therefore, this paper does not advocate thought anarchy, but it is set forth to logically defend the rejection of consistency when it no longer holds or is even defensible. This attitude of academics with sacred thoughts/ ideas happens to be utterly destructive within the academic sphere where progressive teaching and learning pedagogies must be taken into consideration. Not only that the academics themselves will benefit if they embrace a necessary change but also the students will benefit from the progressiveness and non-ideological teaching of their teachers/ lecturers. In my view, it seems very important that at some time academics rationally accept the change of times and accept that their ideas lack sacredness and universal eternity. Having this understanding of academic rationality, I wish to put forth some skeptical views of Bagwan Rejneesh with regard to ideological ideas that claim sacredness even when they have become obsolete.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 7 (2) (2023)
Keywords: Ideological; Consistency; Contradictions; Decolonization; Defense; Ideology; Cognitive consistency; Autonomy and independence movements; Academia